cos 2 альфа + sin 2 альфа * tg альфа

cos 2 альфа + sin 2 альфа * tg альфа

  • cos2alpha+ sin2alpha*tg2alpha
    По формулам:

    1) cos2alpha=cos^{2}alphasin^{2}alpha

    2) sin2alpha=2*cosalpha * sinalpha

    3) tgalpha= frac{sinalpha}{cosalpha}

    Подставив это вс, получаем:
    cos^{2}alpha-sin^{2}alpha+2sin^{2}alpha =cos^{2}alpha+sin^{2}alpha=1

  • cos2a=cos^2a-sin^2a

    sin2a=2sina*cosa

    tga=sina/cosa

    cos^2a-sin^2a+2sina*cosa*sina/cosa=cos^2a-sin^2a+2sin^2a=cos^2a+sin^2a=1

Внимание, только СЕГОДНЯ!
Ссылка на основную публикацию
2018